Mathematical modeling of heat and mass transfer processes in a reciprocating engine of a vehicle with a hybrid powertrain - Fedіr Abramchuk; Vitaliy Krivda; Olha Sakno; Valentyna Olishevska; Kostyantyn Kornilenko; Olena Sakno (Transport Technologies)
Automotive transport plays a crucial role in the functioning and development of any country's economy. In Ukraine, it accounts for over half of passenger transportation and three-quarters of freight transportation. A promising development direction is using electric and hybrid vehicles in transportation logistics. It also fosters advancements in battery production technologies, components of hybrid power units, recycling, and the country's transportation infrastructure. Modern vehicle hybridization combines the advantages of traditional internal combustion engines (ICE) and electric drives. The efficiency of hybrid power units can be considered from design and thermodynamic perspectives. The design approach requires the development of new materials and manufacturing technologies, necessitating significant resource expenditures. The thermodynamic approach involves modeling and optimizing thermal processes occurring in the ICE within hybrid power units. The aim of this study is to identify opportunities for improving heat and mass transfer processes in a reciprocating engine to ensure the energy efficiency of a vehicle's hybrid power unit. Heat and mass transfer processes in the ICE are described by a system of differential equations that account for heat transfer in various environments (working gas, cylinder walls, coolant), considering key parameters such as wall temperatures, gas temperatures, heat transfer coefficients, and combustion kinetics. Several scenarios were examined to study the overall heat and mass transfer process. The first scenario assumes constant temperatures of gases and ICE walls, resulting in a steady heat transfer coefficient. The second scenario involves overloading, leading to increased heat loss through the walls and elevated thermal stress on the cooling system. The third scenario considers a decrease in ambient temperature. This study modeled the dependence of engine wall temperatures over time for these three operating conditions, enabling control of thermal modes and prediction of ICE performance to enhance the efficiency of the vehicle's hybrid power unit. It was found that increasing the temperatures of gases and walls affects engine operation duration, the effectiveness of recovered heat utilization, and the optimization of hybrid power unit performance. The more heat recovered during engine operation, the longer it operates with minimal heat loss and maximum efficiency.